A Meta-Analysis of the Effect of Exercise Rehabilitation Care on Cardiac Function in Patients with Chronic Heart Failure. (4th July 2022) - Lv, Dawei
Abstract : Aims . Effect of systematic exercise rehabilitation nursing on patients with chronic heart failure. Materials and Methods . From January 1, 2021, to March 22, 2006, a comprehensive search was conducted on China Knowledge Network (CNKI), Wanfang, VIPERS (VIP), China Biomedical Literature Database (CBM), PubMed, Cochrane Library, EMBASE library database, and clinical registry to obtain the literature on the impact of exercise rehabilitation nursing on cardiac function of patients with chronic heart failure. From January 1, 2006, to March 22, 2021, the literature of randomized controlled trials (RCTs) on the effect of exercise rehabilitation nursing on cardiac function in patients with chronic heart failure was collected. According to the inclusion and exclusion criteria, literature screening, data extraction, and quality evaluation were carried out. Cochrane system assessor manual version 5.0 was used for quality assessment, and Review Manager Version 5.3 was used for meta-analysis. Results . A total of 9 articles were included, including 752 patients. Meta-analysis showed that exercise rehabilitation nursing had a significant effect on cardiac function indexes (LVESV, LVEF, CRP, BNP, and LVEDV) in patients with chronic heart failure P < 0.05 . Conclusion . Exercise rehabilitation nursing has a good effect on improving cardiac function in patients with chronic heart failure. It can improve cardiac function indexes such as left ventricular end-systolic volume, right ventricular ejection fraction, brain natriuretic peptide, and left ventricular end-diastolic volume in patients with chronic heart failure.